Uso de las habilidades sociales comunicativas en estudiantes de la Institución Educativa Pública Bilingüe N° 60375 Nueve de Octubre, San Pablo 2021 - Candeno Cahuachi, Jerson Abelardo (2024)
This research was carried out with the purpose of characterizing the degree of mastery of social and communicative competencies among the students of the Public Bilingual Educational Institution No. 60375 Nueve de Octubre, located in the district of San Pablo, throughout the year 2021. From a methodological perspective, a descriptive approach was adopted, supported by a non-experimental, cross sectional, univariate and field design. The research covered a population and sample made up of 46 primary level students of the aforementioned institution. To collect information, a survey was used, applying a questionnaire that had been validated in advance by specialists in the field. The results obtained indicate that the level of competence in social and communicative skills of the students is distributed as follows: 58.7% have a regular level, 39.1% have a good level, and only 2.2% reach a very good level.